Development and Validation of the Just Culture Assessment Tool for Nursing Education. Issue 5 (September 2019) - Walker, Danielle; Altmiller, Gerry; Barkell, Nina; Hromadik, Lora; Toothaker, Rebecca
Abstract : Background: Patient safety efforts in practice have focused on creating a just culture where errors can be identified and reported, and system remedies created to prevent reoccurrence. The same is not true of nursing education where student experiences with error and the sequelae that follow focus on individual performance. Purpose: The purpose of this study was to adapt the Just Culture Assessment Tool (JCAT) used in practice settings into a valid and reliable instrument to evaluate just culture in academic settings. Methods: A 27-item instrument was adapted for academia. Content validity was established. Reliability was determined in a pilot study with 133 prelicensure nursing students. Results: The scale content validity index (CVI) was calculated at 1. The reliability of the instrument is strong ( α = .75). Conclusions: The CVI and pilot study findings support the use of the JCAT for Nursing Education as a valid and reliable instrument to evaluate student perception of just culture in academia. Abstract : Supplemental digital content is available in the text.